Collaboration Between Parents and Teachers in Overcoming Arabic Language Learning Difficulties Among Children at Min Paya Seunara Sabang - Sarmiwida (Lembaga KITA, 2023)
The mastery of the Arabic language is essential for Indonesia's individuals to meet global challenges. While formal Arabic language programs in Madrasah serve as a primary means for Indonesian children, students at MIN Paya Seunara, Sabang City, face difficulties in learning Arabic. This research explores the collaborative strategies employed by parents and teachers to address these challenges. The study aims to understand the approaches used by parents and teachers in overcoming Arabic language learning difficulties among students. It investigates whether parents and teachers provide attention, guidance, and necessary resources to alleviate and prevent learning obstacles, especially in Arabic language studies. The research, utilizing a descriptive methodology involving literature review and field research, includes 50 students, 1 principal, 1 Arabic language teacher, and 40 parents at MIN Paya Seunara. Findings suggest that positive collaboration between parents and teachers significantly influences students' academic progress. Efforts such as providing support, sufficient learning resources, and guidance play a crucial role. The study concludes that effective collaboration between parents and teachers is instrumental in addressing Arabic language learning challenges. Recommendations include increasing the number of teachers and fostering closer collaboration between school staff and parents for an enhanced educational process.